2019
DOI: 10.1016/j.jsbmb.2019.105413
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulation promotes mitochondrial fusion as a novel mechanism involved in protein kinase compartmentalization and cholesterol transport in human adrenocortical cells

Abstract: stimulation promotes mitochondrial fusion as a novel mechanism involved in protein kinase compartmentalization and cholesterol transport in human adrenocortical cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…Generally, both ligands upregulated or downregulated the same pathways (Figure 3A). For example, the hallmark set for cholesterol homeostasis was upregulated by both ligands, consistent with previous reports indicating that stimulation promotes cholesterol biosynthesis, cholesterol ester uptake, and cholesterol transport [32][33][34][35]. Interestingly, adipogenesis and xenobiotic metabolism were enriched by ACTH stimulation, but not by AngII stimulation.…”
Section: Acth-and Angii-regulated Pathways In Primary Adrenocortical Cellssupporting
confidence: 89%
“…Generally, both ligands upregulated or downregulated the same pathways (Figure 3A). For example, the hallmark set for cholesterol homeostasis was upregulated by both ligands, consistent with previous reports indicating that stimulation promotes cholesterol biosynthesis, cholesterol ester uptake, and cholesterol transport [32][33][34][35]. Interestingly, adipogenesis and xenobiotic metabolism were enriched by ACTH stimulation, but not by AngII stimulation.…”
Section: Acth-and Angii-regulated Pathways In Primary Adrenocortical Cellssupporting
confidence: 89%
“…Mitochondrial dynamics are implicated not only in maintaining the equilibrium of organelles by repairing or eliminating defective mitochondria [31], but also in regulating steroidogenesis [32]. Accordingly, Ang II was demonstrated to promote aldosterone synthesis in H295 cells by increasing fusion of mitochondria and translocation in these organelles of relevant steroidogenic proteins, such as STAR, that is responsible for cholesterol transport from the outer to the inner mitochondrial membrane, and protein kinase C (PKC) ε, mitogen-activated protein kinase (MEK) and ERK, that drive the activation signaling in mitochondria [33]. Whether and how this occurs in APA, where, as mentioned above, Ang II is low, remains to be investigated [11].…”
Section: Effects Of Ang II On the Mitochondria Functionmentioning
confidence: 99%
“…Previous studies have shown that abnormal mitochondrial dynamics can induce abnormal ROS release from mitochondria and cell apoptosis. Several studies have indicated that Ang II can promote apoptosis through mitochondrial fission in a Drp1‐dependent manner 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that Ang II can promote apoptosis through mitochondrial fission in a Drp1‐dependent manner. 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation